The stages of atrioventricular bundle formation in the human embryonic heart - Silkina Yu.V. (Морфологія, 2009)
The origin, stages and histogenetic processes in atrioventricular bundle were investigated. We studied the human embryonic heart from 5 to 12 week of development. Antibodies to neurofilaments, Ki-67, MSA, α-SMA and neuregulin were used. Formation of the primordia of the atrioventricular bundle depends on the chamber formation in early heart. The first morphologic reconstruction in the atrioventricular bundle starts from 5 week of gestational age. In this time we studied proximal and distal primordias, which formed general tract at 7 week. The early human heart was characterized by strong connections with atrioventricular fibrous tissue, left and right septal cuspes of mitral and tricuspidal valves. Formation of the atrioventricular bundle branches has two stages: primary and repeated growth. Median fibers are blind-ended. We suppose that atrioventricular bundle and bundle branches have extracardiac origin. Histogenesis of the atrioventricular bundle contin-ues after 12 week of human development.